ELECTION MEMES AS PERFORMING ARTS AESTHETIC STRATEGIES OF POLITICAL MISINFORMATION IN RAJASTHAN - Maheshwari, Priyanka; Verma, Amit; Vij, Sanjna; Thakur, Jyotsana; Sharma, Abhishika (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper research explores the concept of election memes as a new kind of performing arts that tactically constructs political meaning, emotionality, and information flow misconstructions in Rajasthan. Although memes are commonly defined as humorous digital artefacts, this paper has proposed them as micro-performances, aesthetic events, which are designed to integrate folklore signals, dramaturgical and multimodal symbolism into persuasive political stories. In this sense, election memes are participatory and not merely aesthetical commentary, mobilisation of identities and dissemination of ideological affect. The study relies on digital folklore, semiotics, and performance theory in order to trace the way in which exaggeration, parody, satire, and symbolic motifs code political misinformation. A collection of memes of the Rajasthan election was collected using prominent social media, and then a three-level analysis was performed: (i) visual/semiotic dissection, (ii) textual sentiment and framing analysis of narratives, and (iii) computational clustering of aesthetic and thematic elements. The results demonstrate that meme misinformation works with culturally-instilled aesthetics mechanisms, which include regional humour, folk, and emotionally-charged caricatures, which ensure virality and credibility. Analysis of audience reception also indicates that youth, rural electorate, and partisan audiences are consuming these memes as performances of belonging that tend to support existing prejudices and add to a digital theatre of persuasion.